Hypovitaminóza D, osteomalatický syndrom a homeokinéza kalcia v dĕtském vĕku - Novák, J (Ceskoslovenska pediatrie, 1993)
The author pays attention to hypovitaminosis D in childhood. Despite efforts to eliminate it, its estimated incidence in the first and second year of life is 5-20%. This relatively high incidence in our population as well as in other countries makes hypovitaminosis D one of the most frequent disorders of the child organism. In addition to nutrition-conditioned rickets more than 50 different diseases have been described with rachitic and osteomalatic manifestations.
Keywords: rachitida; osteomalacie; vápník; Calcium; Osteomalacia; Calcitriol; Vitamin D Deficiency; Infant; Humans; nedostatek vitaminu D; kalcitriol; kojenec; Rickets; lidé